2022
DOI: 10.1124/jpet.122.001174
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Inhaled Treprostinil Palmitil, Inhaled and Intravenous Treprostinil, and Oral Selexipag in a Sugen/Hypoxia Rat Model of Pulmonary Arterial Hypertension

Abstract: Treprostinil palmitil (TP), a long-acting inhaled pulmonary vasodilator prodrug of treprostinil (TRE), has beneficial effects in a Sugen5416/Hypoxia (Su/Hx) rat model of pulmonary arterial hypertension (PAH) that compare favorably to the oral PDE5 inhibitor, sildenafil. In this study in male Sprague Dawley rats, a dry powder formulation of TP (TPIP) was compared to inhaled and intravenous TRE and oral selexipag to evaluate inhibition of hemodynamic and pathological changes in the lungs and heart induced by Su/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“… 34 Two studies conducted using the Sugen/hypoxia rat model of PAH compared the hemodynamic effects of TPIP with other vasodilators – oral sildenafil in the first, and intravenous and inhaled treprostinil and oral selexipag in the second. 35 , 36 These studies found at least equivalent efficacy in hemodynamic improvements in Su/Hx rats when comparing TPIP to established pulmonary vasodilators. Additionally, trials in animal models have suggested a higher cough threshold than conventional inhaled treprostinil, promising improved tolerance by reducing one of the drug’s principal adverse effects.…”
Section: Treprostinil Palmitil Inhalation Powder (Tpip)mentioning
confidence: 87%
“… 34 Two studies conducted using the Sugen/hypoxia rat model of PAH compared the hemodynamic effects of TPIP with other vasodilators – oral sildenafil in the first, and intravenous and inhaled treprostinil and oral selexipag in the second. 35 , 36 These studies found at least equivalent efficacy in hemodynamic improvements in Su/Hx rats when comparing TPIP to established pulmonary vasodilators. Additionally, trials in animal models have suggested a higher cough threshold than conventional inhaled treprostinil, promising improved tolerance by reducing one of the drug’s principal adverse effects.…”
Section: Treprostinil Palmitil Inhalation Powder (Tpip)mentioning
confidence: 87%
“…For the conventional evaluation of the lung vascular remodeling, H&E-stained sections were scanned at 40X and used as described previously (17). Briefly, the pulmonary arteries/arterioles visualized from about 20 random fields of view were identified and categorized according to their Feret diameter into small (10–50 µm), medium (51–100 µm), and large diameter vessels (>100 µm); and the percentage of these pulmonary blood vessels demonstrating the presence of a muscular (completely surrounded by a smooth muscle layer, > 90% circumference), semi-muscular (incompletely surrounded by a smooth muscle layer, 10 – 90% circumference) or a non-muscular (no apparent smooth muscle layer, < 10% circumference) appearance were quantified.…”
Section: Methodsmentioning
confidence: 99%
“…Conventional assessment of vessel morphometry consists of visually selecting a limited number of fields of view from H&E-or elastin-stained lung sections in order to manually identify blood vessels (generally up to 50) and to measure the vascular wall thickness for each vessel (2 measurements/vessel). Other also uses a-smooth muscle actin (a-SMA) labelled sections to focus on the medial hypertrophy (16,17). Additional limitations include a global analysis of endothelial cell and/or muscle cell proliferation, as well as the exclusion of blood vessels of irregular shape (non-circular).…”
Section: Introductionmentioning
confidence: 99%